Chewable Tobacco is Significantly Associated with Dental Caries and Periodontitis Among Incarcerated Women in Prison - Hina Shah; Imran Khan; Sibghat Ullah Khan; Jai Kershan; Sanaa Ahmed; Sumbul Ayaz; Ghazala Usman (ziauddin University, 2024)
Background: Substance use is common among vulnerable populations including prisoners. The study aimed to assess the incidence of chewable tobacco and its association with dental caries and periodontal health status among incarcerated women (prisoners). Methods: A cross-sectional study (December 2021 to February 2022) was conducted on prisoners (Central Jail for Women, Karachi). Approval from the Institutional Review Board, JSMU (JSMU/IRB/2021/579) and permission from the Home Department, Government of Sindh (HD/SO(PRS-I)/11-235/2021), was sought before the study. All females (n=131), aged 18-65 years, serving various jail terms, were selected. The data on chewable tobacco, betel quid, paan, and gutka was recorded. Indices, like D (Decayed), M (Missing), F (Filled) teeth (DMFT) and Community Periodontal Index (CPI), were used to assess dental health status. To assess the association between dental caries and periodontal disease severity, ANOVA, Student t-test, and Chi-square was used. A p-value of < 0.05 was considered statistically significant. Results: Out of 131, about 22 (16.8%) prisoners were active smokers. The most consumed substance among participants were chalia 38 (29%), gutka 38 (29%) followed by pan 23 (17.6%) and tobacco 23 (17.6%) with a mean duration of 6.73 (7.72) years ranging between 0-40 years. DMFT score was not found significantly correlated with substance use among study participants (p=0.100). However, the severity of periodontitis observed was significantly (p=0.031) related to chewable tobacco. Conclusion: The study found a significant association between substance use and the severity of periodontitis (p=0.031) highlighting the alarming health status among incarcerated women in the prison. Keywords: Caries; Dental Health; Incarceration; Oral Hygiene; Periodontal; Substance Use.